2016
DOI: 10.1007/s13277-016-5209-5
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 is required for self-renewal and chemoresistance of CD133-positive human colorectal cancer cells

Abstract: There is increasing evidence supporting the cancer stem cell (CSC) hypothesis, which suggests that a population of tumor cells with stem cell characteristics is responsible for tumor growth, resistance, and recurrence as well as drug resistance. In colorectal cancer, the CD133 antigen defines distinct cell subpopulations that are rich in tumor-initiating cells; however, the drug resistance properties of these CD133-positive cells have not been well defined. The breast cancer resistance protein (BCRP)/ATP-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Drug resistance was originally attributed to drug efflux mediated by adenosine triphosphate-binding cassette transporter (8,9). Increasing evidence has indicated the existence of cancer stem cells (CSCs) in breast cancer, and these CSCs are involved in the process of cancer initiation, metastasis, recurrence and therapeutic resistance (3,6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). CSCs have cancer-initiating capability and metastatic potential (4,(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance was originally attributed to drug efflux mediated by adenosine triphosphate-binding cassette transporter (8,9). Increasing evidence has indicated the existence of cancer stem cells (CSCs) in breast cancer, and these CSCs are involved in the process of cancer initiation, metastasis, recurrence and therapeutic resistance (3,6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). CSCs have cancer-initiating capability and metastatic potential (4,(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism of MDR in human cancer is the upregulation of ATP‐dependent drug efflux pumps by ATP‐binding cassette (ABC) transporters, such as P‐glycoprotein (P‐gp) (P‐gp/MDR1 [multidrug resistance 1]/ABCB1), multidrug resistance protein 1 (MRP1) (MRP1/ABCC1), and breast cancer resistance protein (BCRP) (BCRP/MXR [mitoxantrone resistance]/ABCP/ABCG2) . ABCG2 is highly expressed in the blood–brain barrier (BBB) and gastrointestinal tract and plays a role in protection against xenobiotic exposure .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in colorectal cancer it has been shown that the down regulation of ABCG2 inhibited the self-renewal capacity of these cells, enhancing the efficacy of chemotherapic-induced apoptosis [66]. High levels of ABCG2 was found associated to CSC-like phenotype in human melanoma [21].…”
Section: Limitation Of Current Therapies For Metastasismentioning
confidence: 99%